IMPLEMENTATION OF RELIGIOUS MODERATION IN THE QUR’AN: A SOLUTION TO RADICALISM IN INDONESIA - Falah, Muhammad Zulfikar Nur; Setiawan, Ahmad Bayu; Habe, M. ‘Izzuddin Robbani (Tanzil: Jurnal Studi Al-Quran, 2024)
The case of radicalism in Indonesia is considered unknown until now. The existence of cases of radicalism in Indonesia is very worrying and deserves our collective attention. A way to prevent radicalism can be done through the concept of religious moderation. Religious moderation is a concept for preventing acts of radicalism in Indonesia. Religious moderation is a straight attitude that puts forward proportional values as a role of thinking. The distinction between this research and previous studies is the position of the concept of religious moderation associated with the interpretation of the Qur’an as an implication for the prevention of radicalism in Indonesia meanwhile previous studies only focused on researching the concept of religious moderation about social attitudes of the community and not associated with the interpretation of the Qur’an. This research becomes urgent on how the concept of religious moderation in the Qur’an and its implications for the prevention of radicalism in Indonesia. This research uses a library research method, with relevant sources such as books, journals, theses, and dissertations. The results of this research include intergroup disputes that can be used by certain groups to incite violence, this appears as a cultural product of radicalism in Indonesia. An analysis of the concept of religious moderation in the Qur’an has been identified as a solution to deal with radicalism in Indonesia. This explanation directs each individual to develop an attitude of tolerance, and acceptance of traditions fairly, as well as increasing national commitment, which does not require extremism.